Research and Analysis of Out-of-Tolerance Problem in Mold Processing Based on Intelligence. (15th September 2022) - Wang, Juxian
Abstract : Out-of-tolerance is one of the most common problems in mold processing. For the out-of-tolerance problem in mold processing, the cold stamping die for motorcycle fuel tank shell is taken as the research object to solve the problem of out-of-tolerance, that is, easy to occur in the process of mold forming. Based on knowledge engineering, case-based reasoning (CBR) and numerical simulation are combined to study the intelligent design method of stamping die. The factors of overtolerance in stamping die processing are analyzed, and combined with the stamping process, the intelligent design system framework of cold stamping die for fuel tank shells is constructed. Numerical simulation of the double-cover forming (DCF) process of the fuel tank shell shows that sidewall wrinkling and local cracking are the main defects. Through the analysis of orthogonal table data and evaluation indicators, the optimal parameter scheme is F = 250 kN and H = 5 mm. At this time, the interaction effect ( K 2 = 0.738) of the two is the largest. Through test verification, the distribution trend of the simulated thickness is consistent with the experimental thickness, and the deviation range is within 10%. According to the numerical simulation results, the reasoning mechanism of an intelligent design system including instance and rule knowledge is designed, and an uncertain knowledge reasoning algorithm based on the reliability factor is proposed to improve the accuracy of mold size and reduce the overtolerance of the mold.